The Impact of Lower Extremity Fatigue on Lower Quadrant Dysfunction and Health Profile in Hairdressers - İnce Parpucu, Tuba and Ercan , Sabriye and Başkurt, Zeliha and Başkurt , Ferdi (La Medicina del Lavoro, 2023)
Background: Fatigue is also an important occupational condition for hairdressers. Objective: The purpose of this study was to determine the lower extremity fatigue and related factors in hairdressers. Methods: Lower Extremity Fatigue was assessed with 2 questions containing a 5-point Likert scale. Numerical fatigue rating scale was used to assess general fatigue level, visual analogue scale was used to assess occupational satisfaction, Nottingham Health Profile (NHP) was used to assess health profile, and Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) was used to assess lower quadrant pain profile. Results: In the assessment of lower extremity pain, statistically significant difference was found between Fatigue and Non-fatigue groups in waist (p:0.018), right knee (p:0.020), left knee (p:0.019) and right lower leg (p:0.023) parameters. In the lower extremity Weighted Scores, there were significant differences between the fatigue and non-fatigue groups in waist (p:0.0001), right upper leg (p:0.018), left upper leg (p:0.009), right knee (p:0.0001) left knee (p:0.0001), right lower leg (p:0.001) and left lower leg (p:0.002). The difference in the Energy, Pain and Physical Mobility sub-dimensions of the Nottingham Health Profile of the hairdressers in ’Fatigue Group’ was at a significant level. Conclusions: In conclusion, the rate of lower extremity fatigue found in hairdressers in the present study was quite high and lower extremity fatigue was associated with lower extremity pain and health profile.